Cell chemistry and physiology. - Bittar, E. Edward; Bittar, Neville (Principles of medical biology, 1996)
The first section of this volume consists of five chapters to the nature of membrane transport systems. A chapter on secondary active glucose transport has been omitted because this topic is slated to appear in the Nephrobiology module. Chapter 6 deals with oxidase control of plasma membrane proton transport, while chapter 7 addresses the question of how cell volume is regulated. Although we chose not to have a separate chapter covering additional co-transport systems namely, Na+ -K+ -2CI-, KCI, -HCO-3, as well as CI- -HCO-3 exchange and K+ and CI- movements through channels, the role of each in cell volume regulation is emphasized in Chapter 7. Instead of devoting an entire section to the thermodynamics of metabolism, we thought it desirable to have the subjects of medical imaging and NMR of cell metabolism discussed in some detail in two chapters. These are followed by a chapter on the thermodynamic instrument - the calorimeter. Calrimetry allows the measurement of net changes of heat in cells, tissues, organs and whole body. As will be recognized, heat dissipation does not arise only from chemical reactions but also from interactions between macromolecules and conformational changes in protein complexes and mass Ca2+ movement such as that occurring in contracting skeletal muscle. The last chapter provides an account of equilibrium and non-equilibrium thermodynamics and the enthalpy balance method. It reveals that calometric measurements are useful in studies of clinical and toxicological problems.